Exploring the Intersection of Film, City, and Tourism: A Systematic Literature Review - Matarín Rodríguez-Peral, Eva; Gómez-Franco, Tomás; Taborda-Hernández, Ernesto (Street Art & Urban Creativity, 2024)
Tourism is a social phenomenon that has global economic impact. Similarly, cinema has the ability to influence tourism through its representation of different spaces and cities. This representation shapes the public’s perception of these places, making them potential tourist destinations. Cinema can transform unfamiliar spaces into new attractions, whether through romantic narratives or by showcasing locations and scenes that subsequently inspire the audience to recreate them, feeling like protagonists in their own stories. Given its potential impact on tourism, this research poses the following question: What are the key aspects addressed by academic studies that explore the interaction between film, city, and tourism? The objective is to highlight trends in academic research related to the relationship between film, city, and tourism, as well as to explore the various theoretical and methodological perspectives used. This investigation is conducted through a systematic literature review, demonstrating the effects of city representation in cinema on the promotion of prominent tourist destinations. Among the main contributions is the portrayal of the city as a tourist space depicted in film based on the studied scientific literature, along with the opportunity to identify existing knowledge gaps in this field.